In Vivo Differentiation Potential of Epiblast Stem Cells Revealed by Chimeric Embryo Formation - Yali Huang; Rodrigo Osorno; Anestis Tsakiridis; Valerie Wilson (2012)
Chimera formation after blastocyst injection or morula aggregation is the principal functional assay of the developmental potential of mouse embryonic stem cells (ESCs). This property, which demonstrates functional equivalence between ESCs and the preimplantation epiblast, is not shared by epiblast stem cell (EpiSC) lines. Here, we show that EpiSCs derived either from postimplantation embryos or from ESCs in vitro readily generate chimeras when grafted to postimplantation embryos in whole embryo culture. EpiSC derivatives integrate and differentiate to derivatives of all three embryonic germ layers and primordial germ cells. In contrast, grafted ESCs seldom proliferate in postimplantation embryos, and fail to acquire the identity of their host-derived neighbors. EpiSCs do not incorporate efficiently into embryonic day 8.5 embryos, a stage by which pluripotency has been lost. Thus, chimera formation by EpiSCs requires a permissive environment, the postimplantation epiblast, and demonstrates functional equivalence between this cell type and EpiSCs.